The teacher’s self-constructed approaches to collaborate with newcomer parents in the Norwegian elementary reception class - Norozi, Sultana Ali; Moen, Torill (Frontiers in Education, 2022)
In Norway newly arrived immigrant children often start their schooling in special groups called, reception classes. The aim of this study is to examine one particular Norwegian teacher’s perceptions and practices of collaborating with the children’s parents. The empirical analyses are based on a qualitative approach with interviews and video observations of the teacher. Affirming the earlier research about parents-teacher collaboration from Norway, the study shows that the teacher has developed her own practices of parent- teacher collaboration. Contradicting the earlier research, the findings highlight that despite challenges the teacher experiences collaboration with newcomer parents in a positive way. The paper presents examples of the intentional and self-constructed practices the teacher engages in within and outside the classroom to foster mutual learning and parental involvement resulting in a greater support for both the teacher and the parents. In the discussion the teacher´s approaches are not judged as right or wrong, perfect, or imperfect rather appreciated as self-constructed and self-initiated approaches to collaborate with newcomer parents. A main result is that despite of challenges, if the teacher is motivated and has positive/pluralistic perceptions of immigrant pupils and their parents, then s/he finds ways to collaborate with newcomer parents. The paper concludes with teachers’ practice recommendations for schools and some directions for future research.